The impact of the integration process on the emergence of BRICS - Кошелєва, Христина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
Th<span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; color: black; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;" lang="EN-US">is article studies world integration processes and <span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; color: black; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;" lang="EN-US">its<span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; color: black; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;" lang="EN-US">influence on the emergence of BRICS association. Its members Brazil, Russia, India, China and South Africa<span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; color: black; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA;" lang="EN-US"> are the five countries located on three continents, with significant influence both in the region and around the world, and together they have at their disposal a large number of important for the world economy of natural resources